Question of local exploitation of copper ore deposits in the Urnfield time in Poland - Nowak, K.; Stolarczyk, T.; Stos-Gale, Z.; Baron, J.; Derkowska, K.; Derkowski, P.; Miazga, B.; Woodhead, J.; Karasiński, J.; Maas, R. (Frontiers in Earth Science, 2023)
Despite rich deposits of copper in SW Poland, their exploitation in prehistory has not been confirmed, and in the literature it is usually argued that raw materials processed in the Bronze Age were imported. This is despite the same area providing abundant evidence of prehistoric metallurgy including casting moulds, tuyeres or crucibles. The concentration of prehistoric sites in parts of the Sudety Mountains (in particular a region called Pogórze Kaczawskie) rich in copper ores and far from arable land may also indicate prehistoric prospection activities in this area in the search for raw materials. In this paper, we discuss the issue of the provenance of the metal used in SW Poland, an area where metallurgy-related items dated to the Urnfield period (ca. 1300-500/450 BC) are most numerous. Our study utilises historical evidence of pre-modern mining, GIS analysis of prehistoric sites, and lead isotopic analyses conducted on bronze (n=35) and lead (n=1) artefacts found near the copper outcrops in Silesia, and compared with European lead isotope databases. The lead isotopic data for the Zechstein Limestone (Ca1) ores from a local mine and modern black copper from blast furnaces at Leszczyna and Chełmiec in SW Poland were also analysed as reference data (n=6). Our research demonstrates that metal objects in SW Poland were made of copper obtained from various parts of Europe confirming intense contacts of the Urnfield communities but the lead ornaments were sourced from material of local origin providing the first evidence for the provenance of Polish lead.